Extending hope theory: Internal and external locus of trait hope - Bernardo, Allan Benedict I. (Animo Repository, 2010)
Research using hope theory has shown that individual differences in trait hope explain variations in how people attain their goals. But hope theory seems to assume that goal attainment is a purely individual pursuit. In this study, hope theory was extended to include the locus-of-hope dimension, with both internal and external agency in generating plans for pursuing goals. External agents may be one's family, peers, or a supernatural/spiritual being. The locus-of-hope dimensions were defined and validated in two studies with Filipino university students. Study 1 used confirmatory factor analysis to test hypothesized models of the locus-of-hope dimension. Study 2 used confirmatory factor analysis to further validate the model, then used regression analysis to show that the internal and external locus-of-hope dimensions were associated with individual-level individualism and collectivism, respectively. © 2010 Elsevier Ltd.